APPLICATION OF PROBLEMS AND NEEDS IN PALLIATIVE CARE INSTRUMENT - SHORT VERSION (PNPC-SV) FOR ASSESSING THE PALIATIVE CARE NEEDS FOR THE CANCER PATIENTS - Ratih Ayuningtyas Pocerattu; Anggorowati; Chandra Bagus (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Assessment of the needs of palliative care is the first step to know about the picture quality of life and determine interventions to solve problems experienced by patients with chronic conditions and terminal. One of the instruments that can be used is the Problems and Needs in Palliative Care Instrument - Short Version (PNPC-SV). Instrument PNPC-SV examines the 8 dimensions of activity and exercise, physical symptoms, autonomy, psychological, spiritual, financial, and information needs. Objectives: The purpose of this study was to explore the need of palliative care with the use of the instrument Problem and Needs in Palliative Care Instrument - Short Version (PNPC-SV) in cancer patients. Methods: This research uses qualitative method with case study approach. Data collection was conducted by means of questionnaires filled in the assessment of the needs of palliative care (PNPC-SV), then performed in- depth interviews in accordance with the results of the assessment and observation on the 6 participants in the space of oncology in one of hospital in Semarang. Results: The theme results of this research are: (1) Self-acceptance as well as support to the family of the condition of the patient, (2) Influence the patient's psychological to the social environment, (3) the right education to improve the quality of life and (4) The basic components assessment of the needs palliative care should be assessed by the nurse. Conclusion: The assessment which done in a holistic manner can help the nurse to provide nursing care in accordance with the needs of the patient to face the condition of the disease. The needs of the patient in physical, psychological, social and spiritual is very necessary to maintain the balance of her consistency and integrity in the ability to remain accepted, loved and appreciated by others.